Upaya Pengarusutamaan Gender Berdasarkan Permendiknas Nomor 84 Tahun 2008 Di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bangka Belitung - Asmawi, Syilalia; Rahman, Bustami; Hidayat, Novendra (Journal of Social Contemplativa, 2024)
This research aims to analyze how efforts to implement Gender Mainstreaming in Tri Dharma, namely education, research, and community service at the Faculty of Social and Political Sciences (FISIP), University of Bangka Belitung. Furthermore, it also looks at the opportunities and challenges in efforts to implement Gender Mainstreaming into part of the education program. The theory used in this study uses the theory of Van Meter and Van Horn (1975). The research method used is a qualitative method with a descriptive approach with the types and sources of data used including primary data and secondary data. While data collection techniques are interviews, observation, and documentation. The results of this study show that FISIP has efforts in integrating Gender Mainstreaming. The efforts made in education are through the gender course curriculum, public lectures, webinars, seminars, workshops, and collaboration in strengthening the serious commitment of the campus in realizing a model of organizing the Tri Dharma of Higher Education that priotizes Gender Mainstreaming. Furthermore, in research and community service, in line with the Faculty’s field of science and humanities studies, namely social and politics, lecturers and students cannot be separated from studying topics or issues that occur in the community as a discussion in research and community service, which looks at how the relationship and interaction of the community in it. Furthermore, there are several opportunities with the implementation of PUG, which include increasing gender equality in educational access and participation, strengthening research and teaching with a gender perspective, promoting a more inclusive and gender-friendly culture, creating gender-aware physical facilities, improving the image and reputation of the Faculty, strengthening cooperation and there are also several challenges such as the form of regulation, institutional capacity, and pressure from the community in efforts to implement Gender Mainstreaming policies at FISIP, Bangka Belitung University.